2006
DOI: 10.1188/06.onf.761-769
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Disturbances and Quality Of Life in Patients With Advanced Lung Cancer

Abstract: The magnitude of nocturnal sleep disturbance and daytime sleepiness identified in this study reinforces the importance of ongoing screening and effective intervention for sleep-wake disturbances in patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 43 publications
8
58
0
5
Order By: Relevance
“…The Cronbach's alpha for the global GR-PSQI score was 0.76 highly comparable to alphas reported in previous studies in cancer populations (0.75-0.81) [5,6,9,13,18,40] and in Greek patients with advanced cancer (0.80) [25,26]. The alpha coefficient was also high for the factor 1 score, yet low for the factor 2 score probably due to a factor structure consisted of only two components, rendering difficult to achieve good reliability.…”
Section: Discussionsupporting
confidence: 82%
“…The Cronbach's alpha for the global GR-PSQI score was 0.76 highly comparable to alphas reported in previous studies in cancer populations (0.75-0.81) [5,6,9,13,18,40] and in Greek patients with advanced cancer (0.80) [25,26]. The alpha coefficient was also high for the factor 1 score, yet low for the factor 2 score probably due to a factor structure consisted of only two components, rendering difficult to achieve good reliability.…”
Section: Discussionsupporting
confidence: 82%
“…[16][17][18][19] Similarly, sleep disturbances have been shown to adversely affect the QOL in patients with chronic disease. 20 These results are in line with the assumption that sleep affects QOL. 21 Studies using the EuroQol-5 Dimension (EQ-5D) index, which is often used to measure QOL, have demonstrated lower scores in older individuals compared with younger BRIEF SUMMARY Current Knowledge/Study Rationale: While sleep times are important from the viewpoint of health management, few studies have examined the association between sleep time and health-related quality of life using well-established and commonly used generic instruments and the results have been controversial In this study, we examined the associations between self-reported total sleep times and quality of life independent of perceived health status and depressive disorder.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Ssupporting
confidence: 80%
“…Neben der Dokumentation der Blutdruck-und Herzfrequenzverläufe wurden deshalb in dieser Untersuchung als weitere vegetative Stressindikatoren DHEA-S und Prolaktin im Serum sowie Kortisol in Serum und Speichel bestimmt. Darüber hinaus ist bekannt, dass die alleinige Bewertung der Stressreaktionen des Körpers zur Messung von psychischer Beanspruchung nicht geeignet ist [15,20,43]. Da der Patient selbst die sensitivste Informationsquelle darstellt [17,23,31,42], wurde die Beantwortung von Fragebögen zur Selbstbeurteilung der aktuellen Beanspruchung den sogenannten objektivierbaren Stressparametern gegenübergestellt.…”
Section: Vergleich Von Subjektiver Und Objektiver Stressbewertungunclassified
“…So konnte für diese Patientengruppe u. a. gezeigt werden, dass Schlafqualität [43] und Lebensqualität [44] deutlich eingeschränkt sind. Darüber hinaus finden sich bei diesen Patienten höhere Prävalenzen für depressive Erkrankungen und Angststörungen sowie für die Einahme von Antidepressiva und Anxiolytika [11,34].…”
Section: Introductionunclassified